The impact of an amino acid-humus preparation on lawn boning value - Adam Radkowski; Iwona Radkowska; Karen Khachatryan; Michał Kozdęba; Henryk Bujak; Karol Wolski (Scientific Reports, 2025)
Abstract The application of biostimulants in fertilisation has been shown to enhance plant metabolism, stimulate physiological processes, and mitigate adverse environmental and pathogenic stresses. This study, conducted at the Agricultural University of Krakow (2021–2023), evaluated the efficacy of a foliar amino acid preparation enriched with humic acids (L-Amino + ® Humus) on turf quality. Four experimental variants were established: an untreated control (Variant I) and three treated plots sprayed with the biostimulant at 1.0 (Variant II), 2.0 (Variant III), and 3.0 L ha−1 (Variant IV). Higher application rates (Variants III and IV) significantly improved aesthetic turf quality and reduced fungal disease incidence. Compared to the control, Variant IV (3.0 L ha−1) decreased snow mould (Microdochium nivale) infections by 8% and brown spot (Rhizoctonia solani) prevalence by 12%. Variant III (2.0 L ha−1) also demonstrated positive effects, with 6% and 8% reductions in snow mould and brown spot, respectively. Furthermore, the Normalized Difference Vegetation Index (NDVI) and leaf greenness index (SPAD) chlorophyll meter values increased by 6% and 8%, respectively, in Variant IV relative to the control, indicating enhanced leaf greenness and photosynthetic efficiency. Nutrient analysis revealed that Variants III and IV significantly elevated macro- and micronutrient concentrations (e.g., nitrogen, potassium, iron) in plant biomass compared to the control. In contrast, Variant II (1.0 L ha−1) showed no statistically significant improvements in nutrient content or disease resistance. These findings suggest that L-Amino + ® Humus at doses of 2.0–3.0 L ha−1 enhances turf quality, bolsters resistance to fungal pathogens, and improves nutrient assimilation. Lower doses (1.0 L ha−1), however, were ineffective under the tested conditions. The study underscores the dose-dependent efficacy of biostimulants in sustainable turf management.